2008
DOI: 10.1016/j.socscimed.2008.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Crossing two types of implementation intentions with a protection motivation intervention for the reduction of saturated fat intake: A randomized trial

Abstract: Implementation intentions, namely specific plans regarding when, where and how an individual will act, increase the likelihood of action. There is evidence that implementation intentions should be particularly efficacious when combined with motivational interventions. However, this is yet to be tested in relation to the reduction of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 26 publications
4
53
2
Order By: Relevance
“…The study by Prestwich et al revealed that combining MI and II was more effective to decrease saturated fat than MI (32) of the subjects in exercise behavior (42) that is not compatible with the current study findings that can be due to two different factors, because Milne studied exercise and conducted follow-up just for one month compared to six months and nutrition pattern in the current survey. In a meta-analysis implemented by Barnes et al (43), 24 studies were included, 54.2% represented MI resulted in 5% loss of initial body weight that is similar to the current study results with 7% of weight lost.…”
Section: Effectiveness Of MI Compared To Ii Concerning Anthropometriccontrasting
confidence: 83%
See 1 more Smart Citation
“…The study by Prestwich et al revealed that combining MI and II was more effective to decrease saturated fat than MI (32) of the subjects in exercise behavior (42) that is not compatible with the current study findings that can be due to two different factors, because Milne studied exercise and conducted follow-up just for one month compared to six months and nutrition pattern in the current survey. In a meta-analysis implemented by Barnes et al (43), 24 studies were included, 54.2% represented MI resulted in 5% loss of initial body weight that is similar to the current study results with 7% of weight lost.…”
Section: Effectiveness Of MI Compared To Ii Concerning Anthropometriccontrasting
confidence: 83%
“…Authors assume that since this theory is an eligible predictor of dietary (29) and physical activity (30), it seems likely to be an eligible predictor of persons with overweight and obesity. In addition, it is assumed that a person's intention presents a precursor to behavior that exists in several models including PMT; therefore, with regards to several studies (31,32), II can elevate the chance of behavior modification.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation intentions have been shown to be very effective at helping individuals achieve their goals 47,97,98 and, in keeping with MAP, have been shown to be particularly useful in promoting behaviour change when combined with motivational interventions. 99,100 Implementation intentions specify a plan of when, where and how a person is going to, for example, start exercising. This is believed to result in the behaviour being elicited automatically by the relevant environmental cue rather than by a more effortful decision-making process.…”
Section: Model Of Action Phasesmentioning
confidence: 99%
“…Interventions adopting theories of intention such as the theory of planned behavior as a framework to change health-related behavior have not always been successful [28] and are often more effective in changing intentions rather than behavior [23,29]. The adoption of implementation intention as an intervention strategy to change behavior has been shown to be effective in increasing the intention-behavior link and increasing behavioral engagement in a variety of health-related behaviors [30,31] including physical activity [32][33][34], dietary behaviors [35][36][37], cancer screening and self-examination, [38][39][40], and alcohol consumption [41,42].…”
Section: Action Phases Motivation and Implementation Intentionsmentioning
confidence: 99%